THE ROLE OF EMOTIONAL STRESS IN THE FORMATION OF MORBIDITY AND REDUCED QUALITY OF LIFE OF THE URBAN POPULATION IN TERMS OF HYPERURBANIZATION - Бадалова, А.О. (World of Medicine and Biology, 2016)
The work carried out on the bases 3 urban clinics, with outreach to their patients and parents at neighboring institutions (3 schools, 4 kindergartens and nurseries) and workers on 12 commercial facilities and offices. The response has made 1787 questionnaires and school A low level of ES detected in 29,3±1,1% of the population, the average level - at the level of 51.3±1,2% (P